Leveraging Motion Graphic Animations of the Hydrological Cycle to Foster Critical Thinking - Nabila Amalia Alifah; Alfyananda Kurnia Putra (Future Space: Studies in Geo-Education, 2026)
The pedagogical challenge in teaching the hydrological cycle stems from its inherent abstraction and the inability of students to observe these processes in situ. Consequently, the objective of this Research and Development (R&D) study is to engineer a Motion Graphic Animation framework that specifically addresses these visualization deficits. By transforming static concepts into dynamic visual narratives, this media serves as a cognitive tool to bridge the gap between abstract theory and observable reality, thereby cultivating robust critical thinking skills among high school students. The study was conducted as a targeted pilot implementation involving 23 students from Class X IPS at SMA Panjura Malang. This small-scale implementation serves as a necessary developmental step to evaluate the media's effectiveness in clarifying abstract hydrological processes before broader application in diverse geographical education settings. The method used in this study is a qualitative and quantitative percentage descriptive method that adapts the ADDIE development model to produce learning media products The results demonstrate that the motion graphic animation effectively clarifies the complex, non-observable phases of the hydrological cycle, specifically addressing the 'visualization gap' in processes like infiltration, evaporation, and runoff. By providing a dynamic visual representation of these abstract phenomena, the media moves students beyond rote memorization of definitions toward a deeper conceptual understanding. The implementation led to a significant improvement in critical thinking, with 69% of students achieving 'very high' proficiency levels by successfully interpreting and analyzing the systemic nature of water movement.